The Effect Of Exclusive Breastfeeding History And Infant Feeding (PMBA) On The Nutritional Status Of Toddlers Aged 1-5 Years In Sialang Panjang Village - Sonia Sakawati Putri,; Roni Ardian,; Abul Haitsan, (International Journal Of Health Science, 2025)
Toddlerhood is a golden period that requires optimal nutritional fulfillment to support toddler growth and development. Exclusive breastfeeding and proper Infant and Child Feeding (PMBA) play an important role in preventing nutritional problems. The Indonesian Toddler Nutritional Status Survey (2024) reported that 150.2 million toddlers (23.2%) experienced stunting, 42.8 million toddlers (6.6%) experienced wasting, 12.2 million toddlers (1.9%) experienced severe wasting, and 35.5 million toddlers (5.4%) experienced overweight (WHO, 2024). Data from the Sialang Panjang Village Health Center in 2024 showed that there were still cases of malnutrition in 6 toddlers, stunting in 7 toddlers, and underweight in 17 toddlers. To determine the effect of the history of exclusive breastfeeding and Infant and Child Feeding (PMBA) on the nutritional status of toddlers aged 1–5 years in Sialang Panjang Village. This study used a quantitative method with an analytical observational design with a cross-sectional approach. A sample of 91 toddlers was selected using simple random sampling. Data were collected through questionnaires, interviews, and anthropometric measurements, analyzed using the Chi-Square test (p<0.05). The results showed no significant effect of exclusive breastfeeding history on toddler nutritional status (p=0.189). Meanwhile, infant feeding (PMBA) showed a significant effect (p=0.015). Strengthening exclusive breastfeeding education programs and mentoring PMBA practices according to WHO recommendations is needed, involving village health workers to support optimal nutritional status of toddlers.